Presença de alumínio no efluente descartável gerado numa estação de tratamento d´água e suas implicações na qualidade da água do corpo receptor - Meneses, Ana Carolina Lemos Sá Mendes de (2005)
In the treatment for clarification of raw natural surface waters and in conformity with potability standards imposed by the governmental Decree n. 518/2004 from the Health Ministry, some chemicals are employed, and aluminium sulphate is one of them. The water treatment generates solid residues in the sedimentation tanks and filters, which are then discharged directly or not into the water bodies after the washing up of the plant equipment. It was aimed in the present work to evaluate traces of aluminium in residues, generated at an ETA Estação de Tratamento d'Água (a water treatment plant) and their probable impacts on the quality of the outgoing water effluent. This research is perfectly justified since aluminium salts may represent health hazard to local population that either drinks the water or eats freshwater fish. The present investigation was performed in the 'ETA' (water reservoir) of Gramame, managed by the 'CAGEPA Companhia de Água e Esgotos - do Estado da Paraiba' (the water supply company of the State of Paraiba). Besides aluminium in the water effluent from the sedimentation and filtration processes, some physicochemical parameters were also measured, as well as in the water body receiving the effluent, the Gramame River. Collection sites in the river were distributed along 200 m up and downstream the effluent discharge point. The results obtained showed that most of the parameters analyzed in the Gramame River, despite minor oscillations, were maintained within the limits allowed by the Resolution n. 20/86 of the 'CONAMA Conselho Nacional do Meio Ambiente' (the national council for the environment), except for the parameters colour and concentration of aluminium. The concentration of aluminium decreased downstream, but not the colour. Nevertheless, the aluminium concentration in the Gramame River was much higher after the discharge point of the effluent from the 'ETA' than before it. These results make clear the impact of aluminium on the water quality of the river. Therefore, this suggests the need to adopt mitigating measures of such impact from the operating process at the 'ETA' of Gramame, which should also be closely monitored to prevent from contaminating the water and causing risks to human health.